E-meeting system using JSP - Nik Masdiana, Nik Mohamed (2005)
The rapid growth in the application development technology urges the enhancement of functions quality provided in KUKTeM's e-Meeting for secretaries and secretariats. Currently in the KUKTEM e-meeting system, attendees will receive their minute's post-meetings where modifications can only be done then or in the next meeting session. Since the purpose of an on-line e-Meeting system is to save time, this method clearly is in opposed of that.An online real-time e-Minute will instead increase the meeting efficiency and effectiveness plus it will also save time and cost.B-poll will replace ballot papers and it will enable the meeting attendees to get precise and accurate results immediately after polling is over.System Development Life Cycle (SDLC) will be the main methodology used as the process flow for this project. This system will be developed using the advantage provided by the Java Server Page (JSP).The prototype developed will complement and enhance the features of the current KUKTeM e-Meeting System.